Australian local governments and climate emergency declarations: Reviewing local government practice. Issue 3 (30th October 2020) - Chou, Mark
Abstract: In recent years, a growing number of Australian local governments have reaffirmed their longstanding climate leadership by declaring a climate emergency. Indeed, since 2016, when Melbourne's Darebin council became the world's first local government to declare a climate emergency, close to 100 local governments – or a little under one fifth of all Australian local governments – have taken the extraordinary step and made a similar declaration. But although these local government climate emergency declarations have received widespread government and media scrutiny, the precise nature and obligations of climate emergency declarations for local government remain unclear. Indeed, there is currently little analysis and understanding of what obligations local governments incur from declaring a climate emergency, whether those that have made such a declaration have fulfilled their obligations, and whether climate emergency declarations exceed the remit of existing local government environmental and climate roles and policies. This practice insight article seeks to answer these questions in both theory and practice. It finds that, at present, much of the talk about climate emergency by local government may merely be symbolic and broadly aligned with their existing local environmental and climate roles and policies. Abstract : In recent years, Australian local governments have demonstrated their climate leadership vis‐à‐vis the federal government by controversially recognising the escalating climate emergency. But while these local government climate emergency declarations have received widespread government and media scrutiny, the precise nature and obligations of climate emergency declarations for local government remain unclear. Indeed, there is currently little analysis and understanding of what obligations local governments incur from declaring a climate emergency, whether those that have made such a declaration have fulfilled their obligations, and whether climate emergency declarations exceed the remit of existing local government environmental and climate roles and policies. This practice insight article seeks to answer these questions in both theory and practice.